Genotypes and Genomic Regions Associated With Rhizoctonia solani Resistance in Common Bean - Oladzad, Atena; Zitnick-Anderson, Kimberly; Jain, Shalu; Simons, Kristin; Osorno, Juan M.; McClean, Phillip E.; Pasche, Julie S. (Frontiers in Plant Science, 2019)
Rhizoctonia solani Kühn (teleomorph Thanatephorus cucumeris) is an important root rot pathogen of common bean (Phaseolus vulgaris L.). To uncover genetic factors associated with resistance to the pathogen, the Andean (ADP; n=273) and Middle American (MDP; n=279) diversity panels, which represent much of the genetic diversity known in cultivated common bean, were screened in the greenhouse using R. solani anastomosis group 2-2. Repeatability of the assay was confirmed by the response of five control genotypes. The phenotypic data for both panels were normally distributed. The resistance responses of ~10% of the ADP (n=28) and ~6% of the MDP (n=18) genotypes were similar or higher than that of the resistant control line VAX 3. A genome-wide association study (GWAS) was performed using ~200k single nucleotide polymorphisms (SNPs) to discover genomic regions associated with resistance in each panel, For GWAS, the raw phenotypic score, and polynomial and binary transformation of the scores, were individually used as the input data. A major QTL peak was observed on Pv02 in the ADP, while a major QTL was observed on Pv01 with the MDP. These regions were associated with clusters of TIR-NB_ARC-LRR (TNL) gene models encoding proteins similar to known disease resistance genes. Other QTL, unique to each panel, were mapped within or adjacent to a gene model or cluster of related genes associated with disease resistance. This is a first case study that provides evidence for major as well as minor genes involved in resistance to R. solani in common bean. This information will be useful to integrate more durable root rot resistance in common bean breeding programs and to study the genetic mechanisms associated with root diseases in this important societal legume.